The role of acceptor and π-bridge for donor-driven halochromism of D-π-A N, N-dialkylaminostyrylhetarenes. (February 2023) - Gerasimova, T.P.; Sirazieva, A.R.; Katsyuba, S.A.; Kalinin, A.A.; Islamova, L.N.; Fazleeva, G.M.; Shustikov, A.A.; Shmelev, A.G.; Dobrynin, A.B.; Sinyashin, O.G.
Abstract: The photophysical properties of a series of D-π-A chromophores, where D is represented by di- or trialkylaniline moiety, π – vinylene, A - quinoxaline, quinoxalinone, quinoline, benzothiazole and thiophenecarboxaldehyde, have been analyzed upon acidification. In all cases, appearance of the second emission band is associated with protonation of the nitrogen atom in the donor fragment. Nevertheless, the simultaneous appearance of two emission bands at equal amounts of acid is observed only for dyes with a quinoxalinone acceptor fragment, which suggests the crucial role of the latter in providing dual emission upon acidification. The highest pH sensitivity has been achieved for the dye with an ethyl group at the ortho -position of benzene ring relative to the vinylene bridge. In contrast, the variation of substituents at the aniline nitrogen atom, the protonation of which causes the appearance of the emission under acidic conditions, does not lead to significant changes in pH sensitivity. Graphical abstract: Image 1 Highlights: The halochromic properties of a series of donor-π-acceptor N, N -dialkylaminostyrylhetarenes have been studied. The new emission band appearing upon acidification is related with protonation of the nitrogen atom in the donor fragment. The crucial role of the nature of the acceptor fragment in donor-driven halochromism has been shown. Variation of substituents at the nitrogen atom in the donor fragment does not lead to significant changes in pH sensitivity. The combination 'dibutylaminoethylbenzene donor'-π-'quinoxalinone acceptor' in the dye enhances the response to protonation.